PERAN GURU PAI DALAM MENERAPKAN KURIKULUM MERDEKA BELAJAR DI SMAN 6 MATARAM - Maskur, Muh.; Santosa, Sedya (Al-Ulum: Jurnal Pendidikan Islam, 2023)
Education in Indonesia is facing a paradigm shift with the introduction of the Independent Learning Curriculum (KMB). This curriculum provides flexibility and concerns for schools, teachers and students in the teaching and learning process. However, Islamic Religious Education (PAI) teachers have an important role in determining the success of KMB implementation. The aim of this research is to find out the role of PAI teachers in implementing the Independent Learning Curriculum at SMAN 6 Mataram. The research method used in this research is descriptive qualitative. The data collection techniques used in conducting this research were observation, interviews and documentation. Meanwhile, the data analysis used is data reduction, data presentation, and drawing conclusions and the researcher uses data validity testing with Triangulation. The technique is to test the credibility of the data by checking the data from the same source with different techniques. The research results are presented descriptively according to the problem and research objectives. The research results show that SMAN 6 Mataram has implemented KMB well, although gradually. PAI teachers act as learning facilitators and must take part in various supporting programs. Challenges faced by PAI teachers include limited learning resources, increasing digital literacy, integrating religious values, in-depth understanding of the curriculum, KMB-based assessment, alignment with KMB principles, training and support, student diversity, self-evaluation, and professional development. This article provides insight into the role and challenges of PAI teachers in implementing KMB and illustrates how schools and teachers collaborate in facing curriculum changes. Joint efforts from all parties, including teachers, schools and the government, will be the key to success in implementing KMB and improving the quality of education in Indonesia.